Ecological literacy in a context of first-year college students - Bruyere, Brett L., author (Colorado State University. Libraries, 2003)
This research focused on the knowledge and behavior components of ecological literacy as it pertains to a sample of first-year students at a large land grant university. Specifically, a four-point typology of environmentally responsible behaviors for first-year college students was identified that included dimensions related to consumer, disposal, reuse and conservation activities. The results of the typology were subsequently used to develop attitude and behavior scales to determine the viability of a value-attitude-behavior hierarchy as it relates to environmentally responsible behavior of first-year college students.

Attitudes were strong predictors of environmental behaviors, especially in regards to behaviors pertaining to conservation and reuse. Conversely, value orientation had a significant albeit weak predictive relationship of attitudes about environmental behaviors.

In addition, a sample of the students in this study participated in a series of ecological lessons as part of their first-year seminar course. The effect of environmental education was subsequently analyzed to determine the extent to which knowledge of ecological principles, biological cycles and environmental services affected individual values, attitudes about environmental behaviors, and the frequency with which those behaviors were undertaken. The results indicated that knowledge gain had a positive impact on both attitudes and behavior, but minimal effect on values. The effect was strongest on attitudes about consumer behaviors. In nearly all instances, participating in environmental education positively affected attitudes and environmental behaviors.

The results of this research equip university leaders with knowledge and tools to better integrate ecological literacy in the college curriculum and campus life. It provides a basis for ecological knowledge that should be taught in the classroom, as well as environmentally responsible behaviors to be promoted within the various advocacy and outreach efforts by campus organizations and student groups.
Keywords: environmental science; higher education